Teaching, Art and Technology - Richard Janda (CRIFPE - Centre de recherche interuniversitaire sur la formation et la profession enseignante, 2004)
The author draws on a comparison between the role of technology in art and the role of technology in teaching in order to reflect on his own experience with technology and pedagogy. Teachers should no more look down on technique than do artists. But nor should technology become an end in itself.